Teachers’ Perception of Student-Centered Instruction in Public Schools of Baku, Azerbaijan - Mamedova, Taisa; Bayramova, Basti; Yusifova, Leyla; Jafarzada, Lala; Guluzada, Aysu (ADA University, 2025)
There are various teaching and learning methods outlined in the literature that provide the educators with a deeper understanding of how children learn, the possible ways students can acquire knowledge, ​​and different opportunities available for teachers to impart that knowledge. Among these methods, a gradual transition has been noted towards student-centered instruction (SCI) within educational ​​discussions worldwide. This transition is expressed as “a move from directly transferring knowledge from teacher to students to learning through student discovery and construction of knowledge” (Froyd &Simpson, 2008, p.1). It started with the launch of Education ​​for All (EFA) in 1990, which initiated the dissemination of student-centered instruction (SCI), with donor agencies advocating for “learner-centered and participatory” ​​curricula. Since then, SCI has been embraced in various international educational agendas, from the Millennium Development Goals to the Sustainable Development Goals, emphasizing the importance of ​​active learning (Bremner et al., 2022, p.2). In this context, “the SCI is a learning method that places the learner in the center of the learning process. It includes such techniques as substituting active learning experiences for lectures, assigning open-ended problems and problems requiring critical or creative thinking that cannot be solved by following text examples, involving students in simulations and role plays, and using self-paced and/or team-based learning” (Froyd &Simpson, 2008, p.1). Considering the growing emphasis on SCI, Azerbaijan has implemented ​​reforms that highlight the differences between traditional educational programs and modern curriculum. According to the Ministry of Education of the Republic of Azerbaijan (2010), the traditional programs were knowledge-focused and teacher-centered, whereas modern curriculum is more student-centered, improves personal development and addresses the interest and needs of learners. Now, according to state standards of the general education level and programs (curriculum), one of the general requirements for the content of general education is to define ​​content based on the principles of result-oriented, personality-oriented, student-centered, and integrative approaches (Cabinet of Ministers, 2010). This shift is needed because the traditional teaching model in Azerbaijan schools does not promote interactions between teachers and students, nor does it encourage collaboration among students in the educational environment (Sattarova et al., 2023). Moreover, according to data presented in Programme for International Student Assessment (PISA) ​​Azerbaijani pupils show improvement in development of modern competencies including creative thinking, problem-solving, teamwork, ​​inquisitiveness, ​​intercultural skills, and individual initiative; however, there are still some ​​areas where scores remain lower (Sattarova et al., 2023).
Keywords: Education -- Aims and objectives.; Educational evaluation -- International comparisons -- Azerbaijan.; Learner participation in education.; Constructivism (Education).; Curriculum reform.